Os lócus motivacionais da atividade física: um estudo transversal avaliando determinates contextuais - Machado, Vanessa Albanio (2022)
Motivation is able to support the practice of physical activity and indicate readiness for the task, which according to the theory of self-determination vary according to the degree of perceived autonomy. The main objective was to describe the motivational regulations and basic psychological needs for autonomy, competence and belonging involved with the maintenance phase in different types of physical activity and different times within the maintenance phase with adult practitioners of PA. This is a crosssectional study, with convenience sampling through an online survey that evaluated Brazilian adults who practice PA. The participants were evaluated regarding sociodemographic characteristics and the most practiced physical activity, motivational regulations by the Behavioral Regulation in Exercise Questionnaire (BREQ-3) and basic psychological needs (BNP) by the BPNES scale. Participants were adults (aged 18 to 59 years) engaged in some type of PA for 6 months or more. In total, 616 subjects were included in maintenance (practicing for more than 6 months), with a mean age of 34.22 (SD=11.18) years. Cycling practitioners had less external regulation and dance practitioners had less identified regulation when compared to other PA groups, mindful practitioners had greater identified regulation when compared to other PA groups, adventure sport practitioners had greater introjected regulation, greater regulation identified and less satisfaction with the need for autonomy when compared to other types of PA and practitioners of walking/running outdoors had greater satisfaction with belonging when compared to other PA practices. There was a greater presence of external regulations and less satisfaction of basic psychological needs in practitioners in the first six months of maintenance versus practitioners for more than six months. Our findings suggest that some types of PA favor proximity with more internal regulations and better NPB satisfaction and the initial maintenance periods were supported by more controlled stimuli, which support the longevity of the practice of PA.